The «scientific achievement» in the sociology of Colombia: an approach to the state of the discipline - Masías Nuñez, Rodolfo (2019)
This study focuses on the knowledge of «scientific achievement» in Colombian sociology. There are two objectives: to analyze scientific achievement as a particular matter; and examine as an expression of the state of discipline. It seeks to complement the «states of sociology» global approaches, generally tending to observe the evolution of research topics and institutional, pedagogical and methodological developments in the field of sociologists. «Scientific realization» encompasses academic «production» and «productivity», but as a concept it is part of a perspective that locates them in another theory, which enables an alternative interpretation of these same phenomena. The study is based on a sample design whose unit of analysis is the sociologist from the academic plants of the universities with sociology programs. Its source is the resumes that researchers provide to the Colombian National Science System (CVLAC). There is all your academic and scientific information. Signs of a fragmented sociological world are presented in terms of scientific achievement, as a consequence of recent major.